Managerial Strategies for Enhancing Competitiveness and Adapting to Business Environmental Dynamics: A Case Study of CV. Putra Seneja - pandriyani, yosie kristin; Atoillah, Atoillah; Muhimim, Muhimim; Munawaroh, Munawaroh (Implementasi Manajemen & Kewirausahaan, 2024)
This research aims to analyze the managerial strategies implemented by CV. Putra Seneja in increasing company competitiveness amidst the dynamics of a complex business environment. In facing the challenges of globalization, technological developments and regulatory changes, companies implement strategies that include innovation, resource management and adaptation to external changes. This research uses a descriptive qualitative approach, with data collection methods through interviews, participant observation, and documentation on CV. Putra Seneja, Cilegon City. The research results show that the company implements a differentiation and focus strategy, targeting small to medium scale infrastructure projects in the local market. However, the challenges faced include limitations in technology adoption and the impact of government policies on the projects being implemented. This research also highlights the importance of implementing sustainability principles in company operations, including the use of environmentally friendly materials. In addition, the use of digital technology, developing human resource capacity, and adapting to policy changes are key factors in increasing a company's competitiveness and sustainability. These findings are expected to contribute to companies in designing more effective strategies to face global competition and achieve long-term goals.